Neanderthals and Homo sapiens: cognitively different kinds of human? - Pearce, E (Springer, 2018)
Membership of an extensive social network is imperative for human survival. However, maintaining network cohesion is particularly challenging for hunter–gatherers because they are dispersed over large home ranges and need to keep track of absent social partners for extended periods. The archaeological record suggests that compared to Neanderthals, contemporary modern humans maintained social ties between greater numbers of individuals over greater distances. I argue that such differences would have influenced neural development, driving differences in brain structure and the degree of social complexity that each taxon could sustain cognitively. Following recent suggestions that modern humans’ larger parietals might suggest an enhanced ability to create a ‘virtual inner world’, I hypothesise that this capacity allowed them to monitor larger numbers of absent social partners and thus maintain larger dispersed social networks than their Neanderthal counterparts. Larger social networks would have boosted the ability of modern humans to insure against local resource failure, sustain demographic stability and conserve cultural innovations.